2019
DOI: 10.1002/term.2804
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of osteoarthritis progression in mice following intra‐articular administration of simvastatin‐conjugated gelatin hydrogel

Abstract: Simvastatin is clinically used for the treatment of hypercholesterolaemia. This study investigated the effects of the intra-articular administration of a simvastatin-conjugated gelatin hydrogel on osteoarthritis (OA) progression in a murine model. The medial meniscus of the knee joint was de-stabilized to induce OA in 10-week-old mice. Mice were then intra-articularly injected with dimethyl sulfoxide (control), drug-free gelatin hydrogel, simvastatin, or simvastatin-conjugated gelatin hydrogel. At 8 weeks post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 50 publications
0
28
0
1
Order By: Relevance
“…Previously, studies have reported that simvastatin significantly inhibits the IL-1 β -induced production of matrix-degrading enzymes in vitro and protects against the development of cartilage degeneration in OA model mice [46, 47]. It has also been reported that simvastatin triggers the nuclear translocation of Nrf2 in the rat liver [48].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, studies have reported that simvastatin significantly inhibits the IL-1 β -induced production of matrix-degrading enzymes in vitro and protects against the development of cartilage degeneration in OA model mice [46, 47]. It has also been reported that simvastatin triggers the nuclear translocation of Nrf2 in the rat liver [48].…”
Section: Discussionmentioning
confidence: 99%
“…Matsuzaki et al 18 reported that gelatin hydrogels incorporating rapamycin gradually release rapamycin within approximately 2 days in vitro, but they release rapamycin for approximately 10 weeks in vivo 18 . Furthermore, gelatin hydrogels incorporating simvastatin have been reported to exhibit sustained release for at least 3 weeks in vitro and 4 weeks in vivo 19,34 . The present study used EPA‐incorporating hydrogel formulation solubilized in water into gelatin micelles.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, it has great potential for use in medical, pharmaceutical, and cosmetic applications. Because a gelatin hydrogel has the advantages of biological safety and spatial stability, it has been widely used in many clinical studies as a drug delivery system 14,17,21–26 . However, the conventional procedure to prepare GM‐CDDP uses glutaraldehyde or organic solvents that are harmful to the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Because a gelatin hydrogel has the advantages of biological safety and spatial stability, it has been widely used in many clinical studies as a drug delivery system. 14,17,[21][22][23][24][25][26] However, the conventional procedure to prepare GM-CDDP uses glutaraldehyde or organic solvents that are harmful to the human body. Thus, we developed a new procedure using a F I G U R E 4 (A) Representative images of each group in 3D-μCT at 2 weeks after treatment.…”
Section: Discussionmentioning
confidence: 99%